Autoethnographic poetic inquiry: therapeutically engaging with violence toward queers. Issue 2 (3rd April 2019) - Teman, Eric D.
ABSTRACT: Therapeutic applications of poetry provide a powerful means of exploring and portraying lived experiences of queer individuals. In this article, autoethnographic poetic inquiry is used to explore the author's life. Bullying, suicide, moments of strength and weakness, othering, and stifling of voice are some of the issues explored through this poetic journey. The author reflects on each of the poems he has written and roots such explorations in methodological literature of arts-based qualitative research. The overall purpose of the article is to document parts of the author's life as he demonstrates how poetry has begun to help him heal. Through the act of writing poetry and reflecting on the meanings of said poems, the author takes the reader on a journey through his therapeutic healing process.